2000
DOI: 10.1074/jbc.275.11.7787
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of CC Chemokine Receptors by AOP-RANTES

Abstract: RANTES (regulated on activation normal T cell expressed) has been found at elevated levels in biological fluids from patients with a wide range of allergic and autoimmune diseases and is able to attract several subtypes of leukocytes including eosinophils and monocytes into inflamed tissue. Amino-terminal modifications of RANTES produce receptor antagonists which are candidates for blocking this cellular recruitment. Met-RANTES has been shown to modulate inflammation in vivo, while AOP-RANTES is a potent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 46 publications
5
75
2
1
Order By: Relevance
“…However, this apparent redundancy has not been supported by in vivo studies that have instead demonstrated that individual chemokines that activate the same receptor can have unique functions in vivo (2). This may be related to differential chemokine expression in vivo and/or differential receptor activation by different chemokine ligands (3).…”
mentioning
confidence: 88%
“…However, this apparent redundancy has not been supported by in vivo studies that have instead demonstrated that individual chemokines that activate the same receptor can have unique functions in vivo (2). This may be related to differential chemokine expression in vivo and/or differential receptor activation by different chemokine ligands (3).…”
mentioning
confidence: 88%
“…CCR3 internalization in eosinophils and flow cytometric measurements were performed as described elsewhere (13,17). Quantification of CD26 gene expression on keratinocytes using real-time PCR was performed as described previously (18).…”
Section: Cell-based Assaysmentioning
confidence: 99%
“…Human granulocytes were isolated from heparin-anticoagulated venous blood from normal nonatopic healthy or atopic donors using Ficoll (Pharmacia, Erlangen, Germany) density gradient centrifugation as described previously (23). For further purification, granulocytes were resuspended in HEPES-buffered HBSS (Life Technologies, Grand Island, N.Y.), pH 7.4, containing 1 mg/ml BSA (HBSS plus BSA).…”
Section: Eosinophil Isolationmentioning
confidence: 99%
“…RANTES induction of CCR5 down-regulation allows its recycling to the cell surface, whereas the modified RANTES protein AOP-RANTES prevents the re-expression of cell surface CCR5 (22). On the other hand, CCR1 does not recycle after RANTES stimulation (23). CXCR2 has been shown to be degraded in the lysosomal compartment (24) whereas CCR3 appears to follow both fates; it is partially degraded in the lysosomes, but ϳ70% of the receptors recycle (23,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation